2015
DOI: 10.1093/toxsci/kfv185
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Research Article Flavocoxid Protects Against Cadmium-Induced Disruption of the Blood-Testis Barrier and Improves Testicular Damage and Germ Cell Impairment in Mice

Abstract: Cadmium (Cd) causes male infertility. There is the need to identify safe treatments counteracting this toxicity. Flavocoxid is a flavonoid that induces a balanced inhibition of cyclooxygenase (COX)-1 and COX-2 peroxidase moieties and of 5-lipoxygenase (LOX) and has efficacy in the male genitourinary system. We investigated flavocoxid effects on Cd-induced testicular toxicity in mice. Swiss mice were divided into 4 groups: 2 control groups received 0.9% NaCl (vehicle; 1 ml/kg/day) or flavocoxid (20 mg/kg/day ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…showed that Cd decreased FSH levels and reduced LH secretion in the pituitary, thus reducing generation of T . Other studies have shown that Cd increased the levels of LH, FSH, and T in developmental rats . This may be related to exposure routes, doses, times, and the different types of experimental animals used.…”
Section: Cd‐induced Toxicitymentioning
confidence: 93%
See 1 more Smart Citation
“…showed that Cd decreased FSH levels and reduced LH secretion in the pituitary, thus reducing generation of T . Other studies have shown that Cd increased the levels of LH, FSH, and T in developmental rats . This may be related to exposure routes, doses, times, and the different types of experimental animals used.…”
Section: Cd‐induced Toxicitymentioning
confidence: 93%
“…Flavonoids had anti‐inflammatory and antifibrosis effects in the liver . Studies have showed that flavonoids could inhibit the levels of iNOS and COX‐2, promote the vitality of lymphocytes, increase IL‐4 content, and decrease NO content by directly reacting with NO .…”
Section: Mechanism Of Dietary Flavonoids Against Cd‐induced Toxicitymentioning
confidence: 99%
“…Animal studies also suggested that it may be valuable for the treatment of degenerative and chronic conditions, such as Duchenne muscle dystrophy and benign prostatic hyperplasia . Furthermore, this botanically based mixture appears to exert a protective action in cadmium‐induced testicular toxicity and gentamicin‐induced nephrotoxicity . Finally, flavocoxid exhibited neuroprotective effects in rodent models of cerebral ischemia, autoimmune encephalomyelitis, and brain injury …”
Section: Identification Of Novel Targets In the Arachidonic Acid Cascadementioning
confidence: 99%
“…Cadmium, which is one of the most common environmental and occupational metallic toxicants, has also been demonstrated to potentially threaten human health [1-3]. Due to its high toxicity and cumulative effect, Cd easily leads to multi-organ injury, especially to the genital system [4-6]. Compared with other organs, the testes, which are the male gonads, are more vulnerable to toxicants because of their active cell division and metabolism [7-11].…”
Section: Introductionmentioning
confidence: 99%